Being there: protocol for a scoping review of the medical education literature on grief support training for medical professionals - Soklaridis, Sophie (BMJ Open, 2018)
INTRODUCTION: Medical trainees and professionals do not perceive that they are adequately taught the skills to address issues of grief with their patients. Atypical grief responses can prolong suffering, interrupt normal activities and lead to increased morbidity and mortality. Grief training can help physicians cope with feelings about and responses to suffering, loss and death in a way that improves both physician and patient/family wellness. This scoping review will describe the current landscape of grief training worldwide in medical school and residency and in continuing professional development in the disciplines of paediatrics, family medicine and psychiatry. The ultimate goal is to help physicians support patients experiencing grief. METHODS AND ANALYSIS: The study design has been adapted from Arksey and O’Malley’s review methodology. We will work with an information specialist who will run searches in six multidisciplinary databases. To supplement the search, we will scan the reference lists of included studies. Two levels of screening will take place: a title and abstract review for articles that fit predefined criteria and a full-text review of articles that meet those criteria. To be included in the review, articles must report on grief training for medical residents and professionals in the fields of paediatrics, family medicine and psychiatry. Two investigators will review each article and extract data. ETHICS AND DISSEMINATION: Research ethics approval is not required for this review. We plan to share the findings through national and international medical education conferences and to publish the results in a peer-reviewed academic journal. We have the support of several directors of medical education at our institution who are interested in the growing focus on humanism in medical education as a way of decreasing burnout among medical students, residents and faculty.